Mechanical fatigue in aluminium at elevated temperature and remaining life prediction based on natural frequency evolution. Issue 8 (30th January 2015) - Khan, M. A.; Khan, S. Z.; Sohail, W.; Khan, H.; Sohaib, M.; Nisar, S.
ABSTRACT Fatigue is one of the principle damage mechanisms in materials especially at elevated temperatures. It possesses a great influence on the material properties and the possible working life. In this work, a novel technique for the analysis of fatigue at elevated temperature is suggested. Material fundamental frequency and its drop are used as the key parameters to predict the remaining useful life of a selected shape specimen, which is operated under low‐cyclic fatigue loading at elevated temperature. Experiments are performed on aluminium 1050 with two different lengths of a non‐prismatic cantilever beam at room temperature, 100, 200 and 300 °C, respectively. The experimental data is further transformed in to an empirical correlation that can predict specimen useful life. The error in this life prediction is less than 5%, and it reduces more once the frequency drop is increased.